Analysis of Generic Structure and Recount Text Understanding in Eighth Grade Students - Nindy Astari Resta Utami; Muhamad Sofian Hadi; Aswir Aswir (Universitas Cokroaminoto Palopo, 2022)
This research is motivated by many challenges faced and often occur when learning online during a pandemic like this. Many of the schools where I conduct teaching and learning activities have experienced the same problem, namely, students' inability to comprehend the material and limited communication between teachers and students. My goal in carrying out this activity at the junior high school where I teach, particularly in English subjects, is to make lessons more enjoyable and understandable for students. The method I employ is to provide material in the form of a video that incorporates animation with the goal of increasing students' interest in seeing the material, particularly the Recount Text material. Many students continue to struggle with the material they have been given, and some students are less careful in completing the assignments they have been given